2012
DOI: 10.5539/ijms.v4n6p44
|View full text |Cite
|
Sign up to set email alerts
|

How Do Smaller Firms Select Foreign Markets?

Abstract: The purpose of this paper was to analyze the internationalization of small and medium-sized enterprises (SMEs) in relation to the international market selection (IMS). To accomplish this, an investigation of the primary factors influencing SMEs' choice when selecting international marketswith a systematic approach way was conducted. In addition we sought to understand whether there was a relationship between the systematic approach in IMS and the characteristics of SMEs. Results revealed that the majority of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 47 publications
(51 reference statements)
0
14
0
1
Order By: Relevance
“…Moreover, these models are not capable of facing all the needs of the company, they have not been tested enough and they are often too complex to be implemented. Indeed, different empirical studies have indicated that firms, and in particular SMEs, usually do not adopt a systematic approach to market selection, because entry decisions are often made by "nonrational" reasons that apparently defy the optimizing logic of the market (Brown and Cook, 1990;Ellis, 1995Ellis, , 2000Lee and Brasch, 1978;Musso and Francioni, 2012;Francioni et al, 2013). Van Hoorn (1979), in a comparison with multinational enterprises, found that SMEs usually have not developed successful administrative policies and procedures, and have an inclination towards adopting opportunistic rather than systematic strategic decisions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Moreover, these models are not capable of facing all the needs of the company, they have not been tested enough and they are often too complex to be implemented. Indeed, different empirical studies have indicated that firms, and in particular SMEs, usually do not adopt a systematic approach to market selection, because entry decisions are often made by "nonrational" reasons that apparently defy the optimizing logic of the market (Brown and Cook, 1990;Ellis, 1995Ellis, , 2000Lee and Brasch, 1978;Musso and Francioni, 2012;Francioni et al, 2013). Van Hoorn (1979), in a comparison with multinational enterprises, found that SMEs usually have not developed successful administrative policies and procedures, and have an inclination towards adopting opportunistic rather than systematic strategic decisions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This study was conducted among SMEs from Italy and it revealed that geographic and cultural/psychic distance did not play such significant role in selecting the international market as implied by other studies (see for example Johanson and Vahlne, 1977). Musso and Francioni (2012) supposed that the reason for their findings may be the fact that Italian SMEs use indirect entry modes when expanding abroad and therefore the distance and culture differences become their external partner's problem. Regarding the psychic distance, Nordman and Tolstoy (2014) added (based on their research conducted among Swedish SMEs) that psychic distance plays an important role in enterprise's ongoing foreign operations rather than in their decisions about market selection.…”
Section: Studies On Uppsala Model Applicabilitymentioning
confidence: 70%
“…Another research performed by Musso and Francioni (2012) was focused on analysing the internationalisation process in relation to international market choice. This study was conducted among SMEs from Italy and it revealed that geographic and cultural/psychic distance did not play such significant role in selecting the international market as implied by other studies (see for example Johanson and Vahlne, 1977).…”
Section: Studies On Uppsala Model Applicabilitymentioning
confidence: 99%
“…Few managers use a systematic approach, especially in SMEs (Musso and Francioni, 2012;Papadopoulos and Martìn Martìn, 2010;Sarasvathy, 2001;Westhead et al, 2001). There is no formalised and structured process in a sequence of steps, as can be seen in the rational market selection approach (Cavusgil, 1985).…”
Section: Perspective Description Theorymentioning
confidence: 99%